MEMANFAATKAN HALAMAN RUMAH UNTUK MENAMBAH PENGHASILAN KELUARGA - Meliantari, Dian (Andhara, 2022)
ABSTRACT This community service activity was carried out in Sumakaju Village Rt 003 Rw 008, Jonggol District, West Java in June 2022. The aim is to provide counseling and training to residents regarding the use of home yards to increase family income with the target being residents of RT 03 RW 08. The method used with lectures and the practice of vegetative propagation (various cuttings and grafts). Evaluation of PKM activities is carried out by comparing the understanding of residents before and after the activity through a questionnaire filled out after the training is completed. The result is that 82% are well aware of vegetative propagation of plants. This PKM of 82% greatly inspired the participants. And 75% of participants are interested in entrepreneurship using the yard to increase family income. The enthusiasm of the participants is 100% wanting PKM like this to continue. The desired themes such as composting household waste, making banana chips of various flavors, planting vegetables and living pharmacies in the yard, fish farming at home. Keywords: post-pandemic, entrepreneur, cuttings, grafts, home business